Pengaruh Penambahan Profil Pada Dinding Silinder Ball-Mill Terhadap Distribusi Massa Serbuk Batu Bata - Mujiono; Ikhwanul Qiram; Gatut Rubiono (Virtual of Mechanical Engineering Article, 2021)
Tube design is one aspect that affects the kinetics of ball motion and material particles on the performance of ball mill machines. Variations in the study include profile diameters of 0.75”, 1” and 1.5” while the number of profiles is 2;3; and 4 trial durations of 7 minutes with 6 crushing balls. Mass characteristics of the milled product on a 16 mesh sieve; 60; and 100. The results showed that there was an effect of variations in the diameter of the barrier profile and the number of profiles on the production capacity of the ballmill machine. From the results of the comparative analysis of the profile diameter and the number of profiles, the highest value was obtained at a diameter variation of 1.5” as many as 4 profiles in the number of balls 6 with an experimental time of 7 minutes with a production capacity of 17% mesh 16, mesh 60 15.6% and mesh 100 of 22.6%. The results have also shown the p erformance of the ballmill machine against product loss at smaller particle dimensionsKeywords: Ball mill, ball count, time length, tube wall profile